Importación de bienes de consumo y la actividad comercial de la región Loreto, periodo 2014 - 2018 - Guzman Yalta, Cecilia (2021)
This research is proposed as a premise that imports of consumer goods stimulate commercial activity in the Loreto region. The objective of this thesis was to determine the correlation between the importation of consumer goods and the commercial activity of the Loreto region, in the period 2014 - 2018. For this, this Quantitative, Correlational and Non-Experimental design. The investigation concludes that there is no relationship between imports of consumer goods and commercial activity, having obtained a Correlation Coefficient that was r = 0.656297723, a result below 0.75. In the same way, the Coefficient of Determination was R2 = 0.430726701; very far from 1; This shows that there is no correlation or determination between imports of consumer goods and commercial activity in the Loreto region. The importation of consumer goods was mainly explained by the acquisition of Non-Durable Goods which amounted to US $ 18.40 million, equivalent to 93.40% of the total value. The importation of Non-Durable Goods showed a variable behavior in the five years of study, achieving an average annual growth of 26.32%. The Commerce activity is considered one of the two most important economic activities in the region, having had a growing trend during the period under study.